MATERNAL PRACTICE IN PROVIDING COMPLEMENTARY FOOD FOR INFANTS AGED 6-12 MONTHS TO PREVENTS STUNTING INCIDENCE IN CIKUNIR VILLAGE - Apriasih, Hapi; Yunie HR, Chanty; Rahmidini, Annisa; Fitriani, Sinta (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Stunting is currently still a health problem that needs to be resolved, where one of the contributing factors is providing poor nutritional intake in food or Complementary Breast Milk (MP-ASI) to children under two years old. The aim of this research is to determine the implementation of the practice of giving MP-ASI to mothers who have babies aged 6 - 12 months in an effort to prevent stunting in Cikunir Village. This type of quantitative research uses descriptive methods, with a population of 52 mothers with babies aged 6-12 months. The research results showed that 77% or 40 respondents did not pay attention to how to give MPASI properly and correctly, where the majority of mothers gave MPASI in non-neutral environmental conditions and fed for more than 30 minutes, while there were 5 variables, namely texture, frequency, variety, portion. and cleanliness is appropriate. Increasing communication of information and education by all health service settings starting from Village Midwives assisted by cadres is very important to increase the understanding of mothers of toddlers about the practice of feeding MPASI to toddlers.